When all goes as planned: a case study of Hajj and the best crisis communication strategies for practitioners planning mega-events - Saud A. Alsulaiman; Terry L. Rentner (Humanities & Social Sciences Communications)
Abstract This case study examined how the Kingdom of Saudi Arabia (KSA) managed the 2018 Hajj season, one of the largest worldwide gatherings, to identify prominent communication strategies utilised in a large event. The two-way symmetrical communication and the renewal discourse theory served as theoretical frameworks. A thematic analysis was utilised to analyse communication content, news articles, and tweets. It is almost impossible to know whether the KSA intentionally applied Grunig’s two-way symmetrical communications theory; nevertheless, the results suggested that KSA operated in a way that followed Grunig’s theory. The findings showed how the KSA learned from past mistakes and incorporated Grunig’s two-way symmetrical communication model to implement best public relations practices for a successful 2018 Hajj season. This case study provided various perspectives on how employing communication strategies can help manage a significant event successfully.